قانونِ اسلامی کی تشکیلِ جدید۔۔۔علامہ محمد اقبال اور علامہ محمد اسد کے افکار کا مطالعہ - محمد ارشد (FIKR-O NAZAR فکر ونظر, 2012)
This article seeks to examine the principles and methodology for the reconstruction of Islamic law as proposed by Allama Dr. Muhammad Iqbal and Allama Muhammad Asad (1900-1992) an Austrian convert to Islam. Allama Iqbal vehemently argued for the revival of ijtihad and advocated for the reconstruction of Islamic law. He also laid down a methodology and expounded principles for the task. Asad was deeply influenced by Mufti Muhammad Abduh, Rashid Riza and Dr. Muhammad Iqbal. He was encouraged by Iqbal to assume the daunting task of exposition of Islamic constitutional law as well as the elaboration of a methodology for the reconstruction of Islamic law. Asad denounced the trend of taqlid very harshly and emerged as a vehement protagonist for the revival of the spirit of Ijtihad and independent reasoning. With the emergence of Paksitan he was appointed as Director of the newly created Department of Islamic Reconstruction. Asad formulated a blueprint of Islamic constituion, laid down a scheme for the Islamization of the newly emerged state of Pakistan and suggested a methodology for the reconstruction of Islamic Law. He also vehemently advocated for the codification of Islamic law. Asad called, not just for a partial reformation of the existing corpse of Islamic fiqh and law, rather advocated for the exercise of independent reasoning and a thorough reconstruction of Islamic law, based only on the nusus of the Qur'an and Sunnah. He has endeavoured to redifine the concept of nass. He has also suggested a thorough critical evaluation of the hadith corpse and compilation of an authentic collection of ahadith. The princilple of maslaha has a vital significance in Asad's methodology. Asad, in his proposed methodology, discards the existing schools of Islamic law, and has also rejects the notion of talfiq.